2009
DOI: 10.1007/s11802-009-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary phosphorus on the growth and body components of juvenile Synechogobius hasta

Abstract: The effect of dietary phosphorus on the growth and body components of juvenile Synechogobius hasta was determined. Different percentages of dietary phosphorus (0.63, 0.77, 0.93, 1.06, 1.22 and 1.36) were tested by feeding the fish (body weight, 15.81 g ± 0.32 g; 20 individuals each group; 3 groups each percentage) at a surplus of 5%-10% above satiation for 35 d. Dietary phosphorus did not significantly affect the specific growth rate, feed intake, feed conversion ratio and protein efficiency rate. Nitrogen ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 29 publications
5
7
1
1
Order By: Relevance
“…The whole body ash and phosphorus have been commonly used as indicator of dietary phosphorus status in fish nutrition studies (Skonberg et al., 1997) and frequently used for determining minimum phosphorus requirements (Brown et al., 1993; Ketola and Richmond, 1994; Mai et al., 2006). A positive correlation was observed between dietary phosphorus and ash, calcium and phosphorus concentration of whole fish, scutae and vertebrae in our study, which is consistent with other reports (Luo et al., 2009). The requirement of dietary phosphorus of 1.04 and 0.87% based on the phosphorus content of scutae and whole fish was higher than 0.50% based on the WGR, previous studies showed that requirement estimates based on phosphorus accumulation in the body tissue tend to be higher than those based on growth rate (Brown et al., 1993; Ketola and Richmond, 1994; Vielma et al., 2002; Mai et al., 2006).…”
Section: Discussionsupporting
confidence: 93%
“…The whole body ash and phosphorus have been commonly used as indicator of dietary phosphorus status in fish nutrition studies (Skonberg et al., 1997) and frequently used for determining minimum phosphorus requirements (Brown et al., 1993; Ketola and Richmond, 1994; Mai et al., 2006). A positive correlation was observed between dietary phosphorus and ash, calcium and phosphorus concentration of whole fish, scutae and vertebrae in our study, which is consistent with other reports (Luo et al., 2009). The requirement of dietary phosphorus of 1.04 and 0.87% based on the phosphorus content of scutae and whole fish was higher than 0.50% based on the WGR, previous studies showed that requirement estimates based on phosphorus accumulation in the body tissue tend to be higher than those based on growth rate (Brown et al., 1993; Ketola and Richmond, 1994; Vielma et al., 2002; Mai et al., 2006).…”
Section: Discussionsupporting
confidence: 93%
“…These findings coincided with the results reported by Nordrum et al (1997), Satoh et al (2003) and Luo et al (2009). Rodehutscord (1996) Whole body ash content (%) Y = 1.59 + 5.11 X -3.01 X 2 R 2 = 0.77 0.85% increase of phosphorus intake.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, phosphorus deficiency leads to reduced whole body phosphorous concentration in other studies Baeverfjord et al 1998;Luo et al 2009). Whole body ash content increased with increasing dietary phosphorus from 0.43 to 0.90% and then declined with further increasing dietary phosphorus level.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations